Green Space and Child Weight Status: Does Outcome Measurement Matter? Evidence from an Australian Longitudinal Study - Taren Sanders; Xiaoqi Feng; Paul P. Fahey; Chris Lonsdale; Thomas Astell-Burt (Journal of Obesity)
Objective. To examine whether neighbourhood green space is beneficially associated with (i) waist circumference (WC) and (ii) waist-to-height ratio (WtHR) across childhood. Methods. Gender-stratified multilevel linear regressions were used to examine associations between green space and objective measures of weight status in the Longitudinal Study of Australian Children, a nationally representative source of data on 4,423 children aged 6 y to 13 y. WC and WtHR were measured objectively. Percentage green space within the local area of residence was calculated. Effect modification by age was explored, adjusting for socioeconomic confounding. Results. Compared to peers with 0–5% green space locally, boys and girls with >40% green space tended to have lower WC (βboys  −1.15, 95% CI −2.44, 0.14; βgirls  −0.21, 95% CI −1.47, 1.05) and WtHR (βboys  −0.82, 95% CI −1.65, 0.01; βgirls  −0.32, 95% CI −1.13, 0.49). Associations among boys were contingent upon age (p  valuesage∗green  space<0.001) and robust to adjustment for socioeconomic variables. The benefits of greener neighbourhoods appeared from age 7, with mean WC and WtHR for boys aged 13 y with >40% green space at 73.85 cm and 45.75% compared to those with 0–5% green space at 75.18 cm and 46.62%, respectively. Conclusions. Greener neighbourhoods appear beneficial to alternative child weight status measures, particularly among boys.